Improvement in Waterlogging Tolerance in Plants via Melatonin - Hashem, Abeer; Almutairi, Khalid F.; Alnafissa, Mohamad; Parray, Javid A.; Karabulut, Fadime; Ayed, Chadha; Abd_Allah, Elsayed Fathi (Apple Academic Press, 2025)
Water stress (drought and water logging) has a significant impact on plant growth and development. There has been minimal research on the bioactive plant hormone melatonin’s impact on water logging stress situations, despite the fact that it has been widely investigated in the context of water shortage stress in a number of plant species. Melatonin controls the levels of nitrogen and reactive oxygen species (ROS), which modifies the molecular defense mechanism and improves plant resistance to water stress. Melatonin and other phytohormone interaction is also a crucial part of plants under drought stress. The aim of this chapter is to provide recent updates on the role of melatonin in the water logging and drought tolerance mechanism by improving physiological, molecular, and anatomical changes and also to discusses the impacts of nitric oxide and hydrogen sulfide (H2S) during the tolerance mechanism. © 2025 Apple Academic Press, Inc.
Keywords: abiotic stress; drought; melatonin; phyto-melatonin; phytohormones; tolerance mechanism; water logging